Enzyme Hydrolysates from Stichopus horrens as a New Source for Angiotensin-Converting Enzyme Inhibitory Peptides - Forghani, B; Ebrahimpour, A; Bakar, J; Hamid, AA; Hassan, Z; Saari, N (Hindawi Publishing Corporation, 2024)
Stichopus horrens flesh was explored as a potential source for generating peptides with angiotensin-converting enzyme (ACE) inhibitory capacity using 6 proteases, namely alcalase, flavourzyme, trypsin, papain, bromelain, and protamex. Degree of hydrolysis (DH) and peptide profiling (SDS-PAGE) of Stichopus horrens hydrolysates (SHHs) was also assessed. Alcalase hydrolysate showed the highest DH value (39.8%) followed by flavourzyme hydrolysate (32.7%). Overall, alcalase hydrolysate exhibited the highest ACE inhibitory activity (IC50 value of 0.41 mg/mL) followed by flavourzyme hydrolysate (IC50 value of 2.24 mg/mL), trypsin hydrolysate (IC50 value of 2.28 mg/mL), papain hydrolysate (IC50 value of 2.48 mg/mL), bromelain hydrolysate (IC50 value of 4.21 mg/mL), and protamex hydrolysate (IC50 value of 6.38 mg/mL). The SDS-PAGE results showed that alcalase hydrolysate represented a unique pattern compared to others, which yielded potent ACE inhibitory peptides with molecular weight distribution lower than 20 kDa. The evaluation of the relationship between DH and IC50 values of alcalase and flavourzyme hydrolysates revealed that the trend between those parameters was related to the type of the protease used. We concluded that the tested SHHs would be used as a potential source of functional ACE inhibitory peptides for physiological benefits.